Dynamics simulation of rolling element bearings considering elastohydrodynamic cage contacts - Seiler, Katrin; Tremmel, Stephan; Wartzack, Sandro; Hahn, Bodo; Plogmann, Michael; Graf-Goller, Oliver (Bearing World Journal, 2016)
Rolling bearings that run under high centripetal acceleration show increased friction in their cage contacts. Hence, the hydrodynamics as well as the deformation of the cage have to be taken into consideration in rolling element bearing dynamics simulations. This paper shows how to consider a full-elastically modelled cage in an elastic dynamics simulation for rolling element bearings to improve the accuracy of simulation results (esp. relating to friction torque). The deformed contact geometry is reconstructed from the cage’s nodes through cubic splines. After that the distance between the deformed cage geometry and the outer ring is calculated, which is considered as the lubrication film thickness. Finally, the contact pressure is calculated depending on the lubrication film thickness by using the short journal bearing theory. The contact calculation is compared to the elastic multi-body dynamics simulation program AVL ExciteTM. Furthermore, the simulation results considering the elastically modelled cage are evaluated to simulation results of a rigidly modelled cage using the rolling element bearings multi-body dynamics simulation program Caba3D. It can be seen that there is a significant influence on the pressure distribution and the friction torque if a rigidly modelled or a full-elastically modelled cage is utilized. The hydrodynamics and the cage’s elasticity should not be neglected in rolling bearing dynamics simulations for bearings that run under high centripetal accelerations.
Keywords: Simulation; Wälzlager; Elastohydrodynamik; Dynamik; Mehrkörpersimulation; MKS